Community Participation in Marine Tourism Development at Olele Village - Rahmawaty Baderan; Sri Nuryatin Hamzah; Lis M Yapanto (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2020)
This study aims to determine the participation of the community in the development of marine tourism in the Village District Olele Kabila Bone Bone Bolango District. The method used in this research is qualitative method with descriptive design. The results showed that community participation in marine tourism development in Olele Village consists of 3 aspects, namely the involvement of the emotional aspects of decision making, social involvement that is maintaining water resources, providing services and security, supervising or monitoring marine tourism, and involvement in terms of Economy that is managing or utilizing marine tourism. Keywords: community; participation; marine tourism.